2012
DOI: 10.3928/01477447-20120919-30
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical and Medical Treatment of Rhizopus Osteomyelitis Following Hematopoietic Cell Transplantation

Abstract: Mucormycosis has been reported in otherwise healthy individuals; however, it is primarily seen in immunocompromised patients, such as those with diabetes mellitus, malignancy, or chronic graft-versus-host disease, and has a high mortality rate. Because most cases of mucormycosis are associated with contiguous rhinocerebral infection, only 5 cases of isolated musculoskeletal Rhizopus infection have been reported in the literature. One patient underwent hematopoietic cell transplant, which resulted in a fatal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The most common pathogens of the Mucorales that caused bone and joint infections were Rhizopus species (15 cases) [19][20][21][22][23][24][25][26][27][28][29] followed by Apophysomyces elegans (four cases) [30][31][32][33] , Mucor species (three cases), [34][35][36] Cunninghamella bertholletiae (two cases), 37,38 and one case for each Lichtheimia (formerly Absidia) corymbifera 39 and Saksenaea vasiformis. 40 A genus was not specified in eight cases of histologically documented mucormycosis.…”
Section: Etiologymentioning
confidence: 99%
“…The most common pathogens of the Mucorales that caused bone and joint infections were Rhizopus species (15 cases) [19][20][21][22][23][24][25][26][27][28][29] followed by Apophysomyces elegans (four cases) [30][31][32][33] , Mucor species (three cases), [34][35][36] Cunninghamella bertholletiae (two cases), 37,38 and one case for each Lichtheimia (formerly Absidia) corymbifera 39 and Saksenaea vasiformis. 40 A genus was not specified in eight cases of histologically documented mucormycosis.…”
Section: Etiologymentioning
confidence: 99%
“…In other reported cases, there were no instances where amphotericin-loaded cement spacers were used after arthroscopic ACL reconstruction; however, a unique colored cement (Fig. 4-C) has been used to treat Rhizopus osteomyelitis 9,12 . An in vitro study showed that amphotericin-impregnated cement generated a more stable long-term supernatant concentration than flucytosine and fluconazole 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal treatment led to eradication of the disease [12]. A successful treatment of RM osteomyelitis of the right tibia in an immunocompromised patient was presented by Vashi [9]. …”
Section: Discussionmentioning
confidence: 99%
“…The prognosis and outcome of invasive mucormycosis in patients with immune deficiency or hematologic malignancies is generally rather poor [1, 4, 8]. However in most reported cases fatal outcome could be prevented [8, 9]. …”
Section: Introductionmentioning
confidence: 99%